2022
DOI: 10.21776/ub.jpa.2022.010.04.3
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Preferensi Konsumen Susu Pasteurisasi Pulsed Electric Field “Milkaya” Di Cv Milkinesia Nusantara

Abstract: Ponorogo menjadi satu dari 38 daerah terbesar yang menghasilkan susu di Jawa Timur, namun konsumsi olahan susu sapi masih kurang. Mengetahui preferensi konsumen dan menetapkan atribut yang paling diperhatikan berdasarkan persepsi konsumen terhadap produk susu pasteurisasi menggunakan teknologi Pulsed Electric Field (PEF) “Milkaya” hasil produksi CV Milkinesia Nusantara adalah tujuan dari riset ini. Atribut produk yang dipakai adalah varian rasa, kemasan, harga, dan lokasi pembelian. Lokasi ditentukan dengan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…According to respondents, the price of UHT Ultra Milk Flavor is relatively affordable for students, but among these choices, respondents prefer prices ≤IDR 5.000 and prices >IDR 5,000 are not liked by respondents. Consumers logically prefer lower prices (Ramadhani, Priyanto, Estiasih, & Putranto, 2022). The study had limitations including, this research only focusing on one brand for UHT milk products and using generation Z samples at first university scope, the sample is not valid enough to be generalized on a large scale because the research was only conducted in 1 university.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to respondents, the price of UHT Ultra Milk Flavor is relatively affordable for students, but among these choices, respondents prefer prices ≤IDR 5.000 and prices >IDR 5,000 are not liked by respondents. Consumers logically prefer lower prices (Ramadhani, Priyanto, Estiasih, & Putranto, 2022). The study had limitations including, this research only focusing on one brand for UHT milk products and using generation Z samples at first university scope, the sample is not valid enough to be generalized on a large scale because the research was only conducted in 1 university.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research examined preferences for packaged liquid milk but focused on household consumers, the research found that the preference for milk packaging of household consumers in the District of Jaten is Mocca flavor, the price is ≤IDR 5.000 per pack, brand well-known, box/box packaging, and has clear expiration information, the most prioritized attribute by consumers in a row is information expiration, price, taste, brand, and packaging (Nugroho, Mukson, & Setiawan, 2021). Ramadhani, Yulistiani, Priyanto, Estiasih, and Putranto (2022) also studied milk preferences but for pasteurized types of milk, in this study, it was found that consumers like PEF "Milkaya" pasteurized milk with chocolate flavor, sold at Milkaya outlets for IDR 4.000, the most considered attribute sequentially is taste, location of purchase, selling price, and packaging. Pertiwi, Harisudin, and Setyowati (2017), this study also used Ultramilk products as research objects but this study focused on Ultra Milk as a whole not focusing on Ultra Milk Flavor (flavor variants studied are UHT Full Cream Milk, Mocca flavored milk, Strawberries, UHT Low Fat High Calcium Chocolate, UHT Low Fat High Calcium Milk), consumer preferences in the modern market in Surakarta City are the condition of the milk when purchased is not cold, Ultra Milk with the chocolate flavored, promotions through television advertisements, and 1000 ml packaging sizes, the attributes that are most considered by consumers are taste attributes, furthermore the analysis used Fishbein Multi attribute not using Conjoint Analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of processed livestock products needs to be given to the female students of the dormitory because the prospects for the growth of processed livestock products are currently increasing. According to Ramadhani et al (2022), milk processing is one of the businesses that can be developed. The process of raising the value of milk by processing pasteurized milk is viable to run on a larger business scale.…”
Section: Resultsmentioning
confidence: 99%
“…Saat ini, belum dicantumkan beberapa pengujian berdasarkan SNI seperti pengujian cemaran mikrobiologi, kadar lemak, kadar protein dan lain-lain karena terbatasnya fasilitas sarana dan prasarana serta sumber daya manusia. Mutu organoleptik menunjukkan bahwa produk dari CV Milkinesia Nusantara dengan brand "Milkaya" yang beredar di pasaran dapat diterima konsumen dan memiliki preferensi masing-masing yang dapat disimpulkan bahwa kualitasnya masih baik (Ramadhani et al, 2022).…”
Section: ) Pengujian Mutuunclassified